Successful and Less Successful Psychotherapies Compared: Three Therapists and Their Six Contrasting Cases - Werbart, Andrzej; Annevall, Amanda; Hillblom, Johan (Frontiers in Psychology, 2019)
Despite the general effectiveness of bona fide psychotherapies, the number of patients who deteriorate or fail to improve is still problematic. Furthermore, there is an increased awareness in the field that the therapists’ individual skills make a significant contribution to the variance in outcome. While some therapists are generally more successful than others, most therapists have experienced both therapeutic success and failure in different cases. The aim of this case-series study was to deepen our understanding of what matters for the therapists’ success in some cases, whereas other patients do not improve. How do the patients and their therapists make sense of and reflect on their therapy experiences in most successful and unsuccessful cases? Are there any distinctive features experienced by the participants at the outset of treatment? To explore these issues, we applied a mixed-method design. Trying to keep the therapist factor constant, we selected contrasting cases from the caseloads of three therapists, following the criterion of clinically significant symptom reduction or non-improvement at termination. Transcripts of 12 patient interviews and 12 therapist interviews (at baseline and at termination) were analyzed, applying inductive thematic analysis and the multiple-case comparison method. The comparisons within the three therapists’ caseloads revealed that in the successful cases the patient and the therapist shared a common understanding of the presenting problems and the goals of therapy, and experienced the therapeutic relationship as both supportive and challenging. Furthermore, the therapists adjusted their way of working to their patients’ needs. In the non-improved cases, the participants presented diverging views of the therapeutic process and outcome. The therapists described difficulties in the therapeutic collaboration but not how they dealt with obstacles. They tended to disregard their own role in the interactions and to explain difficulties as being caused by the nature of their patients’ problems. This could indicate that the therapists had difficulty in reflecting on their own contributions, accepting feedback from their patients, and adjusting their work accordingly. These within-therapist differences indicate that taking a “third position” is most needed, and seems to be most difficult, when early signs of a lack of therapeutic progress appear.